Study on the application of ultrasonic wave in the removal of microbiofouling on PMMA surface. Issue 3 (6th July 2021) - Zheng, Liang; Zeng, Yufan; Li, Yuefan; Zheng, Jing
Abstract: Ultrasound has been used for antifouling on the surface of medical devices or food utensils, but it is rarely applied in marine anti‐biofouling on underwater instruments. To understand whether ultrasonic antifouling is suitable for underwater optical windows, the effect of ultrasonic conditions including frequency, power and duration on the removal of microbiofouling on the surface of polymethyl methacrylate (PMMA), a type of common optical material, was investigated in this study by three‐factor and three‐level orthogonal experiments. Before and after the ultrasonic treatment, both surface morphology and fouling degree of PMMA samples immersed in Escherichia coli suspension and seawater were characterized and quantified using laser scanning microscope. The results showed that ultrasonic treatment can effectively remove microfouling from the PMMA surface under suitable conditions. Ultrasonic technology has a great potential for the control of microfouling on the marine optical instruments. When compared with power and duration, ultrasonic frequency has a more significant effect on antifouling efficacy of ultrasound. It is useful for PMMA samples exposed to seawater within 2 days to conduct an antifouling treatment under the condition of an ultrasonic frequency of 20 kHz, ultrasonic power of 40 W, and ultrasonic duration of 7 min.